The Effectiveness of Oral Stimulation on the Suction Reflex in LBW Babies in the Perinatology Room at RSUD dr. Abdul Rivai Berau - Suarni, Suarni; Wardani, Desi Ayu; Sinaga, Sumiati; Suwanto, Suwanto (Journal of Midwifery and Nursing, 2024)
Efforts to treat Low Birth Weight (LBW) babies to increase body weight while in hospital is by providing direct breast milk; however, there is a weakness in suction power in LBW babies. Oral stimulation is necessary to increase the suction reflex to overcome this. This study aimed to determine the effectiveness of oral stimulation on the sucking reflex in LBW babies. This was a pre-experimental study and One Group Pre-Test – Post-Test design without a control group. The population was LBW babies in the Perinatology Room at dr. Abdul Rivai Hospital has 30 babies, based on the Roscoe formula, and has a sample of 20 people. Data analysis used the Friedman test. Characteristics of respondents: mostly gestational age 28-36 weeks (60%), female gender (60%), baby weight between 1,500-2,499 grams (55%), mother's age > 35 years (50%), mother's education graduated from high school (47.1%), parity of multiparous mothers (60%) and mother's occupation as housewife (60%). The sucking reflex in LBW babies before being given oral stimulation was completely lacking by 20 respondents (100%). The sucking reflex in LBW babies after being given oral stimulation was perfect for 20 respondents (100%). Oral stimulation was influential on the sucking reflex in LBW babies (p-value = 0.000 < ?: 0.05). This indicates that oral stimulation is effective on the sucking reflex in LBW babies. Hospitals are expected to make oral stimulation of Standard Operational Procedure for routine activities carried out by nurses and physiotherapists to improve the sucking reflex in LBW and LBW babies.